A Study of the Tenth Grade Students’ Narrative Writing Achievement at SMAN 2 Jember - Ariani, Musli; Lazuardin, Zenela; Putra, Bambang Arya Widja (EFL Education Journal, 2016)
This research was intended to describe the tenth grade students’ narrative writing achievement at SMAN 2 Jember. The area and subjects of this research were chosen purposively by using purposive method. The research design was descriptive study. The research data were obtained by test, interview, and documentation. Based on the research finding dealing with the result of the tenth grade students’ narrative writing achievement at SMAN 2 Jember, it was found that there were 2 students (5,13%) who were categorized as excellent, 13 students (33,33%) who were categorized very good, 12 students (30,77%) who were categorized good, 12 students (30,77%) who were categorized as average, and no student (0%) who were categorized fair, poor, and very poor. This means that the tenth grade students’ narrative writing achievement at SMAN 2 Jember was categorized good.